2016
DOI: 10.1016/j.ccell.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Molecular Differences in Cancer between Male and Female Patients

Abstract: Summary An individual’s sex has been long recognized as a key factor affecting cancer incidence, prognosis and treatment responses. However, the molecular basis for sex disparities in cancer remains poorly understood. We performed a comprehensive analysis of molecular differences between male and female patients in 13 cancer types of The Cancer Genome Atlas and revealed two sex-effect groups associated with distinct incidence and mortality profiles. One group contains a small number of sex-affected genes, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
253
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(267 citation statements)
references
References 66 publications
11
253
2
1
Order By: Relevance
“…Hexokinase 1 (HK1), conversely, was slightly increased in females relative to males (1.1-fold, P = 0.02). Together, this was consistent with previous findings of a weak sex effect on transcript expression in the TCGA LGG dataset (13). However, we were interested in whether there might be glycolytic subtypes within each sex that correlated with survival, specifically.…”
Section: Glycolytic Gene Expression Stratifies Risk In Gliomassupporting
confidence: 78%
See 1 more Smart Citation
“…Hexokinase 1 (HK1), conversely, was slightly increased in females relative to males (1.1-fold, P = 0.02). Together, this was consistent with previous findings of a weak sex effect on transcript expression in the TCGA LGG dataset (13). However, we were interested in whether there might be glycolytic subtypes within each sex that correlated with survival, specifically.…”
Section: Glycolytic Gene Expression Stratifies Risk In Gliomassupporting
confidence: 78%
“…a recent multidimensional analysis of molecular differences in cancer between males and females determined strong sex effects in the presence of mutations, DNA methylation, transcript, and protein expression among renal, bladder, liver, lung, head and neck squamous, and thyroid cancers, but a weak sex effect in low-grade and high-grade gliomas (13). These findings suggest that there are alternative molecular mechanisms, perhaps related to metabolism, that may explain the sex disparity seen in brain cancers that are otherwise invisible to global molecular profiling studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first pan-cancer study investigating these molecular signatures was reported [6]. In this study, Yuan et al performed a comprehensive characterization of common and unique molecular features in male and female patients across 13 major tumor types.…”
mentioning
confidence: 96%
“…In this study, Yuan et al performed a comprehensive characterization of common and unique molecular features in male and female patients across 13 major tumor types. They integrated The Cancer Genome Atlas (TCGA) pan-omics profiles of six molecular data types: somatic mutations, somatic copy-number alterations, DNA methylation, mRNA expression, microRNA expression, and protein expression [6]. Using a propensity score, they extracted two sex-effect groups with molecular features from their analysis [6], which was consistent with patient gender as a prognostic factor in cancer according to the National Comprehensive Cancer Network (NCCN) Clinical Practice Guideline in Oncology.…”
mentioning
confidence: 99%
See 1 more Smart Citation